Ecosystem and Biodiversity of Amazonia 2021
DOI: 10.5772/intechopen.94179
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of Wild Fruits from the Amazon Region of Ecuador: Linking Diversity and Functional Potential of Lactic Acid Bacteria with Their Origin

Abstract: Subtropical wild fruits are a reservoir of microbial diversity and represent a potential source of beneficial microorganisms. Wild fruits provide essential nutrients, minerals, and antioxidants that contribute to human health. Many of these wild fruits are used by indigenous peoples for medicine and food, but there is yet an unexplored potential in the study of their properties and benefits. Wild fruits from the Amazon region and their associated active substances or bacterial communities can prevent disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Previously, we showed that LAB strains isolated from wild fruits possess a unique portfolio of enzymes that allow them to metabolize various compounds and present specific metabolic traits as a result of their microenvironmental origin ( Tenea et al, 2020a ). However, the presence of many gene sequences responsible for carbohydrate and amino acid transport and metabolism is considered an important probiotic characteristic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that LAB strains isolated from wild fruits possess a unique portfolio of enzymes that allow them to metabolize various compounds and present specific metabolic traits as a result of their microenvironmental origin ( Tenea et al, 2020a ). However, the presence of many gene sequences responsible for carbohydrate and amino acid transport and metabolism is considered an important probiotic characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Genome analysis showed the presence of the gene glpK_1 , encoded for glycerol kinase, a key enzyme participating in the regulation of glycerol uptake and metabolism. The ability of UTNGt21O strain to metabolize glycerol and to utilize the α-galacto-oligosaccharides (αGOS) family, d-melibiose [α-Gal-(1→6)-Glu], as well as the raffinose-family oligosaccharide (RFO) d-raffinose was previously detected by employing biochemical miniaturized fermentation tests ( Tenea et al, 2020a ). The results suggested the capacity of this strain to adapt to different niches because of its high genome flexibility, which points this strain as good candidates for functional food design or other biotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, some strains harbor naturally CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) arrays and Cas associated proteins, which grant the capacity to be converted into a tool for genome editing [ 12 ]. Most LAB species used as probiotics or antimicrobial producers are of human or animal origin, and recently, several scientific documents indicated the probiotic potential of LAB species isolated from unconventional sources such as fruits, vegetables, juices, and grain products [ 8 , 13 , 14 ]. Among Lactobacilli, Lactobacillus plantarum is a potential candidate species [ 1 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the microbiota of wild tropical fruits draws our attention [ 14 ]. Theobroma grandiflorum , commonly known as white cacao, Amazonian cacao, or copoazú, is a perennial tree typical of the tropical humid forest, which has its origins in the Brazilian Amazon region and belongs to the Malvaceae family.…”
Section: Introductionmentioning
confidence: 99%